Preparation of ferroelectric BaNb2O6 the urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of BaCl2, NbF5 and urea in required ratio (the ratio of total metal cations to the urea is five) is heated on a water bath at 100 degrees C. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of BaNb2O6 (BN), as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 85 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 900. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides